(untitled) (LACCEI, 2024)
According to the INEI, the companies producing plastics in Peru have increased by 27.65% in the period from 2015 to 2020 in the city of Lima-Peru, being the most representative both in number of companies and in their annual sales, which are 352,514 soles on average. Likewise, it is important to emphasize the millions of soles that companies invest in importing machinery to be able to work the plastic product, however, statistics presented in this source (INEI, 2021) mention that only 11% of companies use the total of installed capacity, which is a significant figure that must be taken into consideration. For this reason, this article will thoroughly address the problems caused by delays when delivering orders in a company in the plastic sector. The company under study has a low order fulfillment rate of 57.38%, which represents 11% of the company’s total costs. To improve this ratio, the TPM tools and its preventive and autonomous maintenance pillars will be used, as well as the use of the SMED tool to reduce delays in the production process. The implementation of the tools lasted 18 weeks at a cost of S/ 30,216. Finally, the result of the implementation of TPM and SMED was positive, since it was possible to improve the downtime of the machines by 70% and increase productivity by 42%.